Climate change lengthens southeastern USA lightning‐ignited fire seasons. (11th July 2019) - Fill, Jennifer M.; Davis, Corey N.; Crandall, Raelene M.
Abstract: Trends in average annual or seasonal precipitation are insufficient for detecting changes in the climatic fire season, especially in regions where the fire season is defined by wet–dry seasonal cycles and lightning activity. Using an extensive dataset (1897–2017) in the Coastal Plain of the southeastern United States, we examined changes in annual dry season length, total precipitation, and (since 1945) the seasonal distribution of thunder‐days as a correlate of lightning activity. We found that across the entire region, the dry season has lengthened by as much as 156 days (130% over 120 years), both starting earlier and ending later with less total precipitation. Less rainfall over a longer dry season, with no change in seasonal thunderstorm patterns, likely increases both the potential for lightning‐ignited wildfires and fire severity. Global climate change could be having a hitherto undetected influence on fire regimes by altering the synchrony of climatic seasonal parameters. Abstract : Over the last 120 years, the dry season in the southeastern United States has lengthened by as much as 156 days (130%), with less total precipitation. Less rainfall over a longer dry season, with no apparent change in seasonal thunderstorm patterns, likely increases both the potential for lightning‐ignited wildfires and fire severity. Global climate change could be affecting fire regimes by altering the synchrony of climatic seasonal parameters. See Letter to the Editor on: https://onlinelibrary.wiley.com/doi/10.1111/gcb.15399 ; see also Response to the Editor on: https://onlinelibrary.wiley.com/doi/10.1111/gcb.15457